Conselho Municipal De Educação: um estudo sobre a participação dos conselheiros na gestão do Plano Municipal de Educação no município de Paço do Lumiar/MA - FIGUEREDO, Eweny Cristina Moraes (2020)
This dissertation is located in the line of research History, Educational Policies, Work and Human Formation and in the research group Policies, Educational Management and Human Training of the Graduate Program of the Federal University of Maranhão (UFMA). The theme proposed for analysis was the Municipal Council of Education (CME), through a study on the participation of counselors in the management of the Municipal Education Plan in the municipality of Paço do Lumiar/MA, with the objective of analyzing the participation of the councillors (representatives) of the CME in the management of the Municipal Education Plan (PmE), considering the processes of implementation, monitoring and evaluation in the period 2018-2020. As a theoretical-methodological approach, we chose the qualitative perspective. For the research, we used the following research techniques: bibliographic based on Bordenave (1994), Bordignon (2009), Cury (2006/2008), Demo (1993), Gonh (2008/2011), Lück (2011/2013), Lima (2012), Paro (2007/2017), Pinto (2008) and documentary, from Laws No. 486/2013 on the creation of the CME of Paço; no. 637/2014 establishing the Municipal Education Plan (Pme) of the municipality; no. 475/2013 authorizing the creation of the Municipal Education System; Municipal Organic Law (1997) and the instruments of nonparticipant observation, held at the CME of Paço do Lumiar–MA (research locus), and the interview, applied to the full members of this council. To this do so, we initially analyzed the categories participation, democratic management and municipal council of education; we made an analysis about the SME of Paço do Lumiar, a document that is the center of the municipality's educational policies; we characterize the CME, highlighting the legal and organizational aspects, the profile of the directors, and finally, we present the results of the research, considering the participation of the directors in the management of the SME in the period 2018- 2020, their contributions and challenges. The study pointed out that the CME councillors of the municipality of Paço do Lumiar/MA did not participate effectively in the sME management process. In the period analyzed, the actions of the counselors were mostly dedicated to regularization of municipal schools and authorization of courses. The challenges of participation in the democratic management of SMEs are varied and go beyond the organizational, structural and financial issues of the CME, since they are conditioned, above all, to its limited political, financial and administrative autonomy, since it remains in many cases dependent on the Municipal Department of Education (SEMED) and its primary demands or acting through external provocations.